Preparation and Second-Order Nonlinearity of Organic/Inorganic Hybrid Materials Doped with Organic Chromophore (Journal of Atomic and Molecular Sciences, 2011)
A kind of hybrid material was made through sol-gel process with the PMMA, TEOS, and 4-[N]-ethyl-N-(2-hydroxyethyl) amino-4'-nitro-azobenzene (DR1). And the films of sol were prepared by using the spin-coated method. Through all optical poling, it could be found that there exists an optimum thickness for film. In addition, the higher of sample temperature was, the smaller intensity of SHG was. The experiment showed that the $SiO_2$ network was existent, and hybrid materials significantly improved orientation stability.
Keywords: thin film; all-optical poling; SHG; temperature.